Nouns and Verbs in Parent Input in American Sign Language during Interaction among Deaf Dyads. Issue 4 (1st October 2020) - Fieldsteel, Zoe; Bottoms, Aiken; Lieberman, Amy M.
ABSTRACT: Parent input during interaction with young children varies across languages and contexts with regard to the relative number of words from different lexical categories, particularly nouns and verbs. Previous work has focused on spoken language input. Little is known about the lexical composition of parent input in American Sign Language (ASL). We investigated parent input in ASL in a sample of deaf mothers interacting with their young deaf children (n = 7) in a free play setting. Children ranged in age from 21 to 39 months (M = 31 months). A 20-minute portion of each interaction was transcribed and coded for a range of linguistic features in maternal input including utterance length, sign types and tokens, proportion of nouns and verbs, and functions of points. We found evidence for a significant verb bias in maternal input; mothers produced more verb tokens and unique verb types than any other word class. Verbs were produced more than twice as often as nouns (36% vs 17% of all tokens) and appeared in a higher proportion of utterances than nouns (57% vs. 31% of all utterances). Points were frequent in the input, often serving as pronouns replacing common or proper nouns. Maternal noun and verb tokens increased in frequency with child age and vocabulary. These findings provide an initial step in understanding the lexical properties of maternal input during free play interactions in ASL.